2014
DOI: 10.1021/jp5026762
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Gas Molecules in Graphene Oxide Interlayer: The Role of Water

Abstract: Intercalation phenomena of gas molecules in the interlayer of graphene oxide have been investigated using CO2, CH4, H2, and N2 gases. Intercalation of gas molecules is highly affected by the affinity between the hydrophilic surface of GO and target molecules. Among tested gases, CO2 can only be intercalated. Furthermore, the swelling of interlayer changed the intercalation phenomena. Amounts of intercalated gases are significantly enhanced, and all the gases can be intercalated by retarded dynamics of intercal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 31 publications
5
77
0
Order By: Relevance
“…When CO 2 gas was injected in the water-swollen GO sheets at 5 bar, followed by freezing at À30°C, the interlayer of GO sheets decreased to 9.9 Å (2h: 8.9°, green line). This was because part of the space occupied by water molecules in the GO interlayer, was compressed by the force of the restructuring of the excess water molecules surrounding the GO sheet into ice [22,23]. The crystallization of water molecules into hexagonal ice was confirmed by several peaks (23.1, 24.6, 26.2, 34 and 40.4; green dots) in the CO 2 intercalated GO after freezing (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…When CO 2 gas was injected in the water-swollen GO sheets at 5 bar, followed by freezing at À30°C, the interlayer of GO sheets decreased to 9.9 Å (2h: 8.9°, green line). This was because part of the space occupied by water molecules in the GO interlayer, was compressed by the force of the restructuring of the excess water molecules surrounding the GO sheet into ice [22,23]. The crystallization of water molecules into hexagonal ice was confirmed by several peaks (23.1, 24.6, 26.2, 34 and 40.4; green dots) in the CO 2 intercalated GO after freezing (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…It is important to note that we chose CO 2 gas as the intercalating gas molecule for this study, because CO 2 gas molecules have strong tendency to be intercalated in water-swollen interlayer GO. This is because pre-intercalated water molecules in GO interlayer exhibit strongly reduced dynamic and dielectric constant due to the strong interaction of water with hydrophilic GO basal plane, which leads to the considerable gas storage in water-swollen GO, especially for CO 2 [22,23]. The stored CO 2 molecules were then locked in the interlayers by freezing (at À30°C) the excess water outside the interlayer, thus blocking access to the GO interlayers (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of water was not intensively studied. Recently, Kim et al investigated the effects of water on the intercalation of gas molecules on graphene oxide interlayers [98]. The results revealed that the degree of intercalation was strongly influenced by the interaction between gas molecules and hydrophilic surface of graphene oxide, and only CO 2 could be intercalated in the dried interlayer of graphene oxide.…”
Section: Carbon-based Membranesmentioning
confidence: 99%
“…All of the tested gases could then be intercalated, but the CO 2 could be mostly solvated, surrounded by the intercalated water molecules and partially with functional groups on GO surfaces. Moreover, because the interaction between the intercalated water and GO retards the dynamics of water molecules, enhanced gas storage could be achieved within the intercalated water [ 50 ].…”
Section: Gas Separationmentioning
confidence: 99%